Investigations on Ornithobacterium rhinotracheale in broiler flocks in Elazig province located in the East of Turkey - Ozbey, G; Ongor, H; Turgut-Balik, D; Celik, V; Kilic, A; Muz, A (Czech Academy Agricultural Sciences, 2004)
In the present study, lung, trachea and serum samples from broiler flocks slaughtered at an abattoir in Elazig province located in the East of Turkey were examined for the presence of Ornithobacterium rhinotracheale using culture and enzyme-linked immunosorbent assay (ELISA). The identity was latter proved by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SIDS-PAGE), western blot analysis, and polymerase chain reaction (PCR) assays. A total of 324 serum and 250 lung and trachea samples were collected from 10 commercially reared chicken flocks showing respiratory manifestations. The samples were obtained from different flocks. The causative agent (ORT) was isolated from trachea (1.5%) of five chickens and from both lung and trachea (0.4%) of only one chicken in the bacteriological examination of tissues. The presence of antibodies against ORT was detected in 33 (10.2%) of the 324 sera by ELISA. A 784 bp fragment of the 16S rRNA gene was amplified using specific primers in the PCR. All ORT isolates that were positive by culture were also detected to be positive by the PCR. SDS-PAGE protein profiles of whole cell extracts showed a high similarity for all the isolates with a major band of the molecular weight of 33 kDa (kiloDalton). Results of Western blot analysis indicate four antigenic fractions predominantly with molecular weights of 33, 42, 52 and 66 kDa.
Keywords: Ornithobacterium rhinotracheale; ELISA; SDS-PAGE; western blot analysis; PCR; chicken